Iberic-american and Colombian open access scientific dental journals - Delgado-Troncoso, Jorge Enrique (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the purpose of this study was to identify the Iberic-American open access (OA) scientific dental journals that are included in the regional repositories-indexes SciELO and RedALyC and the most prestigious international indexes, in order to provide an initial inventory and generate questions for future research about the development of dental scientific communication in the region. Methods: This is a descriptive study in which OA scientific journals were searched in SciELO and RedALyC and the indexes Publindex, LiLACS, Latindex (catalogue), Medline, Web of Science (WoS), Scopus, and Google Scholar. Data of variables such as country of publication, journal title, publisher, and indexations were organized in four tables. Likewise, Colombian dental journals included in Publindex were used as a case. Results: There were 13 journals in SciELO and six in RedALyC (only one in both). Three journals are indexed by Medline (all of them Brazilian), nine in Scopus, and two in the WoS. In addition, there were seven dental journals in Publindex. Conclusion: Participation of Iberic-American OA dental journals in the regional and international repositories and indexes is modest. The best ranked journals (indexed by the main international bibliographic services) are published in English, publish a larger number of articles, and are included in SciELO.